ANALYSIS OF SLANGS USED BY THE STUDENTS OF 9A CLASS OF SMP PGRI WRINGINANOM - Anggun Purnomo Arbi; Nur Kalim (Yayasan Hurriah, Banda Aceh, 2022)
Slang is a type of language variation that is used in the informal situation. This study had a goal to describe the type of slang used by the students of 9 A class of PGRI Wringinanom junior high school. The researcher applied a research methodology called descriptive qualitative method because this study described the data in the form of narration. The subjects of this study were 19 students of 9 A class of PGRI Wringinanom Junior High School. Observation was the data collection procedures in this study. The steps of analyzing data in this study were identifying types of slang expression and describing the data. Researcher found 15 expressions of slang that were “alay”, “baper”, “yuk ya”, “ciyus miyapa”, “geje”, “mantul”, “gws”, “otw”, “cabe-cabean”, “ciap”, “86”, “bebeb”, “ajib”, “anjir”, and “bacot”. Researchers found 4 types of slang namely: imitative, acronym, flippant, and fresh and creative.